2009
DOI: 10.1111/j.1600-048x.2009.04500.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning towards tomorrow? Common nightingales Luscinia megarhynchos change and increase their song repertoires from the first to the second breeding season

Abstract: Á R. Mundry, Max-Planck-Inst. for Evol. Anthropol., Leipzig.In many oscines, song repertoire size correlates with male quality and female mate choice, and can vary with age. In a cross-sectional field study in common nightingales Luscinia megarhynchos, one y old birds had substantially smaller repertoires than did older ones. In laboratory experiments males can acquire new song types during this period. This longitudinal field study therefore investigates whether individual nightingales increase their repertoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 33 publications
3
36
0
2
Order By: Relevance
“…In a cross-sectional comparison, Kiefer et al (2006) showed that 1-year old males had smaller repertoires than older males. This result was confirmed by a subsequent longitudinal study (Kiefer et al 2009) showing that 1-year-old males had an increased repertoire the next year.…”
Section: Discussionsupporting
confidence: 87%
“…In a cross-sectional comparison, Kiefer et al (2006) showed that 1-year old males had smaller repertoires than older males. This result was confirmed by a subsequent longitudinal study (Kiefer et al 2009) showing that 1-year-old males had an increased repertoire the next year.…”
Section: Discussionsupporting
confidence: 87%
“…Common nightingales modify the repertoire composition between their first and second year to match those songs that are shared by most individuals within the population (Kiefer et al 2009;Kipper and Kiefer 2010). A similar process could take place in clay-colored thrushes, but more studies are needed to determine if syllable selection is arbitrary or not.…”
Section: Song Plasticity Between Successive Breeding Seasonsmentioning
confidence: 92%
“…Recordings were down-sampled to 22.05 kHz, high pass filtered (0.8 kHz, Butterworth) and amplitude normalized to 75 %. First, we determined repertoire sizes of all males via visual inspection of 533 consecutive songs, equalling approximately 1 h of singing, which has been proven to result in saturated repertoire curves (for details see [34, 35, 44]. Since nightingale song types have been assigned to song categories (e.g.…”
Section: Methodsmentioning
confidence: 99%